Reeling them in: using TikTok and video content to leverage engagement between academic librarians, libraries and students - Humphries, Chelsea (Insights the UKSG journal, 2025)
TikTok is the video-sharing social media platform of the moment. Young people, most often of the age of undergraduate students, are its primary users. Creating a library TikTok profile and sharing video content on the platform is consequently an excellent way for academic librarians and their libraries to engage with their student users. This case study explores the strategy employed at the Ferriss Hodgett Library at the Grenfell Campus of Memorial University for creating and sharing engaging videos on our library's TikTok and other social media channels. Providing a critical evaluation of TikTok use and discussing themes and ideas for video content alongside best practices, this article outlines how short-form videos can be leveraged via TikTok and other video-based platforms to make the academic library and its staff more relevant and approachable, and lay the foundation for building stronger and more meaningful relationships with students. Keywords: academic library, engagement, social media, TikTok